Increasing Customer Loyalty at McDonald's Kemang Through Customer Satisfaction - Naila Umniyyati Rahmah; Parlagutan Silitonga (PT FORMOSA CENDEKIA GLOBAL, 2023)
Customer satisfaction is the core concept of loyalty, meaning that without satisfaction, there will be no loyalty, so it can be said that customer satisfaction is a factor in shaping loyalty. The purpose of this study is to analyze how McDonald's Kemang can win more loyal customers by increasing customer satisfaction focusing on product quality and brand image. 184 customers of McDonald's Kemang are the population of this study. The sampling method uses a nonprobability sampling technique with a purposive sampling approach, because the sample of this study only includes McDonald's Kemang customers. The data collection technique in this study involved distributing questionnaires to respondents. The research findings show that the value of each variable has a positive and significant impact, both directly and indirectly.